2021
DOI: 10.3390/molecules27010001
|View full text |Cite
|
Sign up to set email alerts
|

Three of a Kind: Control of the Expression of Liver-Expressed Antimicrobial Peptide 2 (LEAP2) by the Endocannabinoidome and the Gut Microbiome

Abstract: The endocannabinoidome (expanded endocannabinoid system, eCBome)-gut microbiome (mBIome) axis plays a fundamental role in the control of energy intake and processing. The liver-expressed antimicrobial peptide 2 (LEAP2) is a recently identified molecule acting as an antagonist of the ghrelin receptor and hence a potential effector of energy metabolism, also at the level of the gastrointestinal system. Here we investigated the role of the eCBome-gut mBIome axis in the control of the expression of LEAP2 in the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Beyond feeding, the finding that central LEAP2 can attenuate dopaminergic reward signaling warrants further studies of its effect in different dopamine-related psychiatric disorders, most distinctively addiction disorders where GHSR signaling already have been shown to be affected [17][18][19]48 . Interestingly, LEAP2 appears greatly affected by diet, as shown here and in previous studies 49,50 , as well as by the gut microbiome 51 . Importantly, we show here that even LEAP2 expression in deep brain structures are highly affected by diet.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Beyond feeding, the finding that central LEAP2 can attenuate dopaminergic reward signaling warrants further studies of its effect in different dopamine-related psychiatric disorders, most distinctively addiction disorders where GHSR signaling already have been shown to be affected [17][18][19]48 . Interestingly, LEAP2 appears greatly affected by diet, as shown here and in previous studies 49,50 , as well as by the gut microbiome 51 . Importantly, we show here that even LEAP2 expression in deep brain structures are highly affected by diet.…”
Section: Discussionsupporting
confidence: 86%
“…As such, the current study was limited to only using male mice. Considering that there appears to be some sex-dependent differences in LEAP2 51, 52 , any such differences must be addressed to fully understand the effects of LEAP2. Further, we aimed to investigate the effects of acute central effects of LEAP2, and not the effects of systemic or prolonged elevated LEAP2, which further studies should address.…”
Section: Discussionmentioning
confidence: 99%
“…Through the hepatic-gastric-brain axis (98), Leap2 may impact eating and energy balance. Latest research demonstrated that Leap2 also mediates the outcomes of food consumption and energy metabolism through the endogenous cannabinoid system (eCBome)-gut microbiome (mBIome) axis (106). In summary, LEAP2 can improve diabetes by inhibiting brain intake-related energy metabolism.…”
Section: Effect Of Leap2 On Energy Metabolismmentioning
confidence: 99%
“…The major alterations of eCBs and eCB-like lipid mediators in the brain widely reported in germ free (GF) mice (Manca et al, 2020b), further corroborate the idea that the eCB signaling system mediates many functions of the bidirectional microbiota-gut-brain communication. Even beyond the implications for NDDs, there is now evidence that the complex homeostatic role exerted by the eCB system and eCBlike mediators is including unpredicted functions such as those recently described for the intestinal expression of the liverexpressed antimicrobial peptide 2 (LEAP2), which is partially regulated by eCB system-microbiota interaction and is important for the impact of nutrients on energy metabolism (Shen et al, 2022).…”
Section: Ecbs-microbiota Reciprocal Contamination: Implications For A...mentioning
confidence: 99%